A-181 Comparing Virtual Reality and Analog Prospective Memory Performance. (28th August 2020) - A, Coldiron; L, Smith; J, Helphrey; J, Sawyer; E, Flores; T, Glover; D, Lee; M, Barnett
Abstract: Objective: A virtual reality-based prospective memory task was designed to examine whether a virtual environment would allow for a deeper level of processing and aid prospective memory performance. The purpose of this study was to compare young adults' performance on analog and virtual reality-based prospective memory tasks. Method: Young adult college students (N = 40; ages 18–26) completed both analog and virtual reality prospective memory tasks in the Virtual Kitchen Protocol. Results: A within-subjects analysis of variance found that participants performed better on the analog prospective memory task than in virtual reality, F(1, 39) = 12.46, p = .001. Conclusions: Results suggest that the virtual environment served as a source of distraction rather than a memory aid for young adults' prospective memory ability. However, this added level of distraction may mimic everyday prospective memory settings better than traditional analog tasks, suggesting that virtual prospective memory tasks may be able to better assess everyday prospective memory abilities.